MNC MEDIA GROUP: POLITICAL ECONOMICS ANALYSIS IN COMMUNICATION AND STRUCTURATION THEORY - Muhammad Ainani (Metacommunication: Journal of Communication Studies, 2023)
This paper discusses the construction of media coverage under the auspices of MNC Media. The method in this paper uses a descriptive approach. The analysis is based on the political economy of media theory developed by Vincent Mosco. The theoretical approach used is more specific to structuration theory. The conclusion is that there is a conflict of interest and political interest between Hary Tanoe, the leader of the MNC Group, and his media. Since the MNC Group and the Perindo Party have the same power structure, producing news content through MNC Media is nothing but a political publication of the Perindo Party itself.